A review and comparative analysis of the risk-needs-responsivity, good lives, and recovery models in forensic psychiatric treatment - Lutz, Maximilian; Zani, Davide; Fritz, Michael; Dudeck, Manuela; Franke, Irina (Frontiers in Psychiatry, 2022)
Forensic mental health care primarily focuses on aspects of safety. Treatment is involuntary, and personal rights are highly restricted. Both direct and indirect coercion and significant power imbalances can impede not only the psychological state of inpatients but also their treatment motivation and the therapeutic process in general. However, successful treatment is essential to enable patients to regain their freedom. Therefore, the question arises whether and how health professionals, without disregarding the potential risks, can enable forensic psychiatric patients to experience meaningfulness and self-efficacy in their lives. In offender rehabilitation, the Risk-Need-Responsivity (RNR) model and Good Lives Model (GLM) are widely established theories. The RNR model focuses not only on the risk of recidivism but also on those needs of a person that provoke or prevent criminal behavior and the individual's ability to respond to various kinds of interventions. In contrast, the GLM aims to reduce the risk of re-offending by enabling an individual to live a "good life," i.e., a meaningful and fulfilling life. Originally developed in correctional services, i.e., for offenders without severe mental disorders, both the RNR model and the GLM have also been tested in forensic psychiatric treatment contexts. The Recovery Model is based on the concept of personal recovery in mental health care and is understood as the development of a sense of purpose and mastery in one's own life during the process of coping with the sequelae of a mental disorder. It is a central element of rehabilitation in general, but is also being increasingly applied in forensic psychiatric treatment settings. This review aims to compare the central concepts of the three models, in particular regarding personal development, and the current evidence for their efficacy in mentally disordered offenders.